2013
DOI: 10.5194/bg-10-1893-2013
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses of DMS and DMSP to ocean acidification in Arctic waters

Abstract: Abstract. Increasing atmospheric CO2 is decreasing ocean pH most rapidly in colder regions such as the Arctic. As a component of the EPOCA (European Project on Ocean Acidification) pelagic mesocosm experiment off Spitzbergen in 2010, we examined the consequences of decreased pH and increased pCO2 on the concentrations of dimethylsulphide (DMS). DMS is an important reactant and contributor to aerosol formation and growth in the Arctic troposphere. In the nine mesocosms with initial pHT 8.3 to 7.5, equivalent to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
91
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(116 citation statements)
references
References 70 publications
12
91
7
Order By: Relevance
“…In these mesocosm experiments, the temporal evolution of DMS concentration within a confined natural water volume is investigated under different levels of CO 2 partial pressure with corresponding seawater pH (further information on the method is given in Archer et al, 2013). As in Six et al (2013) we assume a linear decrease in DMS production (P DMS ) with decreasing pH ( Fig.…”
Section: The Marine Biogeochemistry Model Micom-hamoccmentioning
confidence: 99%
See 1 more Smart Citation
“…In these mesocosm experiments, the temporal evolution of DMS concentration within a confined natural water volume is investigated under different levels of CO 2 partial pressure with corresponding seawater pH (further information on the method is given in Archer et al, 2013). As in Six et al (2013) we assume a linear decrease in DMS production (P DMS ) with decreasing pH ( Fig.…”
Section: The Marine Biogeochemistry Model Micom-hamoccmentioning
confidence: 99%
“…Archer et al, 2013; see also the discussion in the Supplement of Six et al, 2013, and references therein). These findings were confirmed by follow-up mesocosm studies in warmer ocean regions such as the coastal waters of Korea or in the sub-tropics off the Canaries (Park et al, 2014;S.D.…”
Section: Introductionmentioning
confidence: 97%
“…The majority of these experimental studies revealed a negative impact of decreasing pH on DMS production (Hopkins et al, 2010;Avgoustidi et al, 2012;Archer et al, 2013;Webb et al, 2016), but some have reported either no effect or a positive effect (Vogt et al, 2008;Hopkins and Archer, 2014). Several hypotheses have been proposed to explain these contrasting results.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors attribute the pH-induced variation in DMS production to an alteration of the physiological properties of the phytoplankton cells or of the bacterial DMSP metabolism (Vogt et al, 2008;Hopkins et al, 2010, Avgoustidi et al, 2012Archer et al, 2013;Hopkins and Archer, 2014;Webb et al, 2015Webb et al, , 2016, whereas others evoke an interaction between the DMSP producers and their grazers (Kim et al, 2010;Park et al, 2014). So far, only one study has looked at the impact of OA on DMS dynamics in the Arctic (Archer et al, 2013). The results of this mesocosm study, conducted near Svalbard, show a decrease in DMS concentrations at low pH, suggesting that OA may significantly reduce DMS emissions to the atmosphere in the Arctic.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of ocean acidification, mesocosms have been used on several occasions for experimental time periods spanning from a few days to a few weeks, and were found to be efficient in studying the effects of this driver over such short time scales (Riebesell et al, 2008. Archer et al (2013) recently showed, during a mesocosm experiment in the Arctic, that with seawater acidification and increased CO 2 concentrations, average concentrations of DMS decreased by up to 60 % at the lowest pH. Inversely, concentrations of dimethylsulfoniopropionate (DMSP), the precursor to DMS, increased by up to 50 %.…”
Section: Introductionmentioning
confidence: 99%